Raman spectra of water in fluid inclusions: I. Effect of host mineral birefringence on salinity measurement. (12th May 2015) - Caumon, Marie‐Camille; Tarantola, Alexandre; Mosser‐Ruck, Régine; Marshall, Craig P.
<x xml:space="preserve">Abstract</x> Raman microspectrometry of water in individual aqueous fluid inclusions can provide chemical information about fluid composition, in particular the concentration of chloride ions. The regular method consists in correlating the deformation of the OH stretching vibration band of liquid water in the region assigned to hydrogen‐bonded OH groups with chloride concentration. In the present study, a set of seven different minerals with various birefringence properties (barite, calcite, celestine, fluorite, kyanite, quartz and siderite) was selected for the analysis of the water band of their hosted aqueous fluid inclusions. The comparison with microthermometry highlighted that any birefringent mineral may affect the determination of salinity carried out by the analysis of the Raman signal of water: the Raman salinity exposed sinusoidal variations when rotating the samples on the microscope stage. This phenomenon was explained by mineral birefringence, and by the polarization properties of the OH stretching vibration band of liquid water and of the spectrometers gratings. A good knowledge of the polarization properties of the optical devices of the Raman spectrometer and a correct positioning of the sample thus result in salinity (chloride concentration) measurements with the same accuracy as classic microthermometry. Copyright © 2015 John Wiley & Sons, Ltd.